Land-vehicle mems INS/GPS positioning during GPS signal blockage periods - T. D. Tan (H. : ĐHQGHN, 2017)
The demand of vehicle navigation and guidance has been urgent for many years. The idea of integrating multisensor navigation systems was implemented. The most efficient multisensor configuration is the system integrating an inertial navigation system (INS) consisting of MEMS based micro sensors and a global positioning system (GPS). In such system , the GPS is used for providing position and velocity whereas the INS for providing orientation. The estimation of the system errors is performed by a Kalm an filter (KF). A serious problem occurs in the INS/GPS system application that is caused by the accidental GPS signal blockages. In this paper, the main objective is to improve the accuracy of the obtained navigation parameters during periods of GPS signal outages using different methods. The overall performance of the system have been analyzed by experim entation data; and results show that these methods indeed improve the quality of the navigation and guidance systems.